Interface matters - Effects of catalyst layer metallurgy on macroscale morphology and electrochemical performance of carbon nanofiber electrodes - Pande Ishan; Ferrer Pascual Laura; Kousar Ayesha; Peltola Emilia; Jiang Hua; Laurila Tomi (Elsevier S.A., 2025)
The effect of catalyst materials and different process parameters on the growth of carbon nanofibers (CNFs) has been widely investigated. Typically, an adhesion metallization is required together with the catalyst to secure adequate attachment to the surface. The interactions within this multilayer structure and their effect on CNF growth and morphology has, however, not been thoroughly assessed. Thus, this work presents the growth behavior, the macroscale morphology, and the basic electrochemical characteristics of CNFs grown on two types of substrates - (1) Si + 80 nm Cr + 20 nm Ni, and (2) Si + 20 nm Ti + 20 nm Ni. Our results show that the macroscale geometric parameters of CNFs can be readily altered by using different adhesive layers. The inherently unstable Ti-Ni interface results in diffusion of Ni towards the silicon wafer to form silicide, which reduces the amount of available Ni for CNF nucleation, and therefore, the population density of fibers is reduced. On the other hand, the Cr-Ni interface results in a larger population density, but the rate of growth is reduced due to diffusion of carbon into the thicker Cr layer. The results are rationalized by using relevant binary and ternary phase diagrams. Further, cyclic voltammetry experiments show that the pseudocapacitance of CNFs shows a correlation with the length and population density of fibers, while the electron transfer kinetics appear nearly reversible for all the electrodes. This simple approach can be used for tailoring CNFs for specific applications by controlling their macroscale geometrical parameters.